Feasibility of Concentrating Solar Power as a Solar Fuel for Electrical Power Stations: A Case Study of Ubari Gas-Power Station in Libya - El-Khozondar, Hala; Andeef, Mostafa; Nassar, Yasser; El-Khozondar, Rifa; Awad, Hilmy (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
This study affirms the economic viability and environmental advantages of employing concentrated solar power (CSP) as an alternative energy source for electricity generation in the gas-fired power plants at the Ubari station-Libya. The main objective of this study is to provide technical and economic information about the solar power tower (SPT) and parabolic trough concentrator (PTC) to the Libyan government and engineers to encourage fostering sustainable development in the region by mitigating oil depletion by a specific percentage and redirecting it towards petrochemical industries with higher economic returns. Utilizing the System Advisor Model program, various technologies for generating electricity from concentrating solar energy were compared, considering diverse hours and storage capacities. The levelized cost of energy served as a benchmark for the comparative analysis. The findings indicate that the CSP technology of the solar power tower field is optimal, constituting approximately 43.6% of the capacity factor. The proposed generation system's ideal design characteristics include a SPT capacity of around 400 MW, a thermal storage tank with a capacity of 11,332 m³, approximately 508 hectares needed for field construction, a project capital cost of approximately $186,102,644, and the levelized cost of energy of about 13.48¢/kWh. The estimated annual crude oil savings amount to about 3,187,726 barrels, equivalent to approximately $243,637,912. The prevention of approximately 1,735,060 tons of CO2 from being released into the atmosphere is associated with an estimated environmental damage cost of about $130,129,247.